A Common Splice Site Mutation Is Shared by Two Families with Different Type 2N von Willebrand Disease Mutations - Nesbitt, I. Mandy; Hampton, Kingsley K.; Preston, F. Eric; Peake, Ian R.; Goodeve, Anne C. (Thrombosis and Haemostasis, 1999)
Using an ELISA-based method to detect type 2N von Willebrand disease (VWD), we found two individuals with absent FVIII binding. Direct sequencing of the FVIII binding region of the von Willebrand factor (VWF) gene showed that one individual had an R854Q substitution whilst the other had a T791M substitution. The very low FVIII binding and the VWF:Ag levels in both individuals suggested a second defect on the other VWF allele. Conformation sensitive gel electrophoresis of polymerase chain reaction amplified DNA was used to detect an additional change in the VWF gene of each patient. Direct sequencing confirmed a previously unreported G to A transition in the donor splice site in intron 25 of both individuals which should result in a null allele. This was confirmed by mRNA analysis. These two individuals therefore have compound heterozygous VWD in which the only expressed allele has a type 2N mutation. In our population, such compound heterozygosity appears to be a significant cause of type 2N VWD.